Factors influence compliance intention behavior on zakat of income among Universiti Malaysia Kelantan staff - Rahim, Rohidah; Abdul Aziz, Rahimah; Omang @ Omar, Rafidah; Supanot, Raihana Tul Amalina (2015)
This paper examines the relationship between factors that influence compliance intention behavior in payment zakat of income among Universiti Malaysia Kelantan (City Campus)Pengkalan Chepa, Kelantan. Related factors under investigation are the zakat distribution management, the islamic awareness and zakat payment system. We use quantitative approach by Cronbach's alpha, correlation, regression and coefficient. We conducted our survey by distribute questionnaire to UMK City Campus staff. Regarding on the result, we found that islamic awareness and zakat system payment have significant relationship with the compliance intention behavior in payment zakat of income among UMK staff (City Campus). However, based on the result that we get, one independent variables which is zakat distribution management doesn't have significant relationship with the compliance intention behavior in payment zakat of income among UMK staff (City Campus)